The POLARBEAR-2 and the Simons Array Experiments - Suzuki,A; Ade,P; Akiba,Y; Aleman,C; Arnold,K; Baccigalupi,C; Barch,B; Barron,D; Bender,A; Boettger,D; Borrill,J; Chapman,S; et al. (Journal of Low Temperature Physics, 2016)
We present an overview of the design and status of the Polarbear-2 and the Simons Array experiments. Polarbear-2 is a cosmic microwave background polarimetry experiment which aims to characterize the arc-minute angular scale B-mode signal from weak gravitational lensing and search for the degree angular scale B-mode signal from inflationary gravitational waves. The receiver has a 365 mm diameter focal plane cooled to 270 mK. The focal plane is filled with 7588 dichroic lenslet–antenna-coupled polarization sensitive transition edge sensor (TES) bolometric pixels that are sensitive to 95 and 150 GHz bands simultaneously. The TES bolometers are read-out by SQUIDs with 40 channel frequency domain multiplexing. Refractive optical elements are made with high-purity alumina to achieve high optical throughput. The receiver is designed to achieve noise equivalent temperature of 5.8 μμ K CMBs√CMBs in each frequency band. Polarbear-2 will deploy in 2016 in the Atacama desert in Chile. The Simons Array is a project to further increase sensitivity by deploying three Polarbear-2 type receivers. The Simons Array will cover 95, 150, and 220 GHz frequency bands for foreground control. The Simons Array will be able to constrain tensor-to-scalar ratio and sum of neutrino masses to σ(r)=6×10−3σ(r)=6×10−3 at r=0.1r=0.1 and ∑mν(σ=1)∑mν(σ=1) to 40 meV.